2015
DOI: 10.5588/ijtld.14.0650
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of idiopathic pulmonary fibrosis in Korea based on the 2011 ATS/ERS/JRS/ALAT statement

Abstract: The incidence of ILD with fibrosis was approximately 23% of overall ILD incidence. IPF incidence was approximately 10% of the incidence of ILD with fibrosis. Based on the new ATS/ERS/JRS/ALAT statement published in 2011, the incidence rate of IPF was 1.7/100,000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 0 publications
1
10
1
Order By: Relevance
“…This study was a retrospective analysis of healthcare big data open systems in Health Insurance Review & Assessment Service (HIRA) and was approved by the authors' Institutional Review Board. HIRA is a government-related organization that has created a proper claims review, and is the quality assessment system for national health insurance (NHI), the public medical insurance system operated by the Korean government [ 12 13 14 ]. The NHI program overviews a compulsory social insurance system covering the entire population.…”
Section: Methodsmentioning
confidence: 99%
“…This study was a retrospective analysis of healthcare big data open systems in Health Insurance Review & Assessment Service (HIRA) and was approved by the authors' Institutional Review Board. HIRA is a government-related organization that has created a proper claims review, and is the quality assessment system for national health insurance (NHI), the public medical insurance system operated by the Korean government [ 12 13 14 ]. The NHI program overviews a compulsory social insurance system covering the entire population.…”
Section: Methodsmentioning
confidence: 99%
“…There was an overall increase in morbidity and mortality in those years. Longevity, regular medical examinations, and increasing use of CT might contribute to changes in the epidemiology of IPF (7). An epidemiological survey in Japan from 2003 to 2007 indicated that the prevalence and cumulative incidence of IPF was 10.0 and 2.23 per 100,000 population, respectively, with 72.7% of cases involving males and an increase in frequency with age (8).…”
Section: Epidemiologymentioning
confidence: 99%
“…Reported incidence rates have been lower (1.3-3.6 per 100,000) in Asia. 66,69,[72][73][74] The incidence of IPF increased progressively in the United Kingdom between 1991 and 2003. 63 Another study cited a sixfold increased incidence of IPF in the United Kingdom between 1978 and 2008.…”
Section: Epidemiology Of Idiopathic Pulmonary Fibrosismentioning
confidence: 99%
“…61 Mortality rates from IPF are markedly increased in the elderly. In the United States, projected deaths (per million) in 2008 were as follows: 18 (age: 45-54); 71 (age: 55-64); 306 (age: [65][66][67][68][69][70][71][72][73][74]; 827 (age: 75-84); 1,380 (age: > 85). 75 Idiopathic UIP is rare in children.…”
Section: Epidemiology Of Idiopathic Pulmonary Fibrosismentioning
confidence: 99%